THE EFFECT OF PRESSURE ON ORDER/DISORDER IN KAOLINITE UNDER WET AND DRY CONDITIONS - Galán E.; Aparicio P.; La iglesia Á.; González I. (My University, 2006)
Well ordered kaolinite was isostatically and uniaxially pressurized up to 13,200 kg/cm2 for 10 min in dry conditions and the effects of pressure on kaolinite order were determined by analyzing the shapes of two-dimensional diffraction bands on X-ray powder diffraction patterns. Increased pressure decreased the percentage of low-defect kaolinite phase, and isostatic pressure proved to be more effective than uniaxial pressure in increasing disorder, e.g. the degree of disorder resulting from 2000 kg/cm2 isostatic pressure was equivalent to that caused by a 3200 kg/cm2 uniaxial pressure. Also, the effect of high pressure was similar to that obtained with lower pressures applied several times (e.g. the effect of applying 8500 kg/cm2 pressure for 10 min was comparable to using 3200 kg/cm2 pressure five times). In addition, six kaolinites of different structural order were isostatically pressurized up to 4000 kg/cm2 for 10 min, both in dry and wet (water) conditions. Under dry conditions, changes in structurally ordered kaolinite were comparable to those cited above whereas kaolinite pressurized in wet conditions showed a moderate improvement in structural order. These results may contribute to our understanding of kaolinite behavior during burial diagenesis and low-grade metamorphism. In addition, these results can also be used in industry to improve kaolin technological properties that depend on kaolinite structural order by application of appropriate industrial pressure processes.
Keywords: EXPERIMENTAL PRESSURE BEHAVIOR; KAOLINITE ORDER DISORDER